2017
DOI: 10.21037/jgo.2017.01.02
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic influence of histopathological regression patterns in rectal adenocarcinoma receiving neoadjuvant therapy

Abstract: Results: A total of 183 patients from two hospitals. The concordance rate between pathologists was good. In total, 18% of the patients showed grade 0 (complete response), 31.7% grade 1, 19.2% grade 2 and 31.1% grade 3 regression. T down-staging was found in 51.9% of the cases. 46 patients recurred and 18 died of disease (median follow-up time: 39 months). We found a statistically significant association between pathological response and pT stage and down-staging. Inflammatory reaction in the tumor bed was sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 17 publications
3
18
0
Order By: Relevance
“…Dworak grade 2, where shrinkage is the main form of regression. This is in line with findings of Fernandez-Acenero [70], who showed that fragmentation was indeed the main pattern of response in the near-complete response group (58%), and that the presence of fragmentation was linked to the absence of downstaging. We can only hypothesize about the more complex interpretation of this reaction pattern and the poor outcome.…”
Section: Near Complete Response Is Associated With a Poor Prognosissupporting
confidence: 92%
See 4 more Smart Citations
“…Dworak grade 2, where shrinkage is the main form of regression. This is in line with findings of Fernandez-Acenero [70], who showed that fragmentation was indeed the main pattern of response in the near-complete response group (58%), and that the presence of fragmentation was linked to the absence of downstaging. We can only hypothesize about the more complex interpretation of this reaction pattern and the poor outcome.…”
Section: Near Complete Response Is Associated With a Poor Prognosissupporting
confidence: 92%
“…The limited size of the fragments is below the power of resolution on imaging and surgical treatment might be irradical, resulting in local recurrences. Three recent studies (289 patients with locally advanced rectal cancer) [68][69][70] showed that fragmentation was present in 40% of cases, while in a study of 45 cT3 patients from Cleveland [44] 80% of cases showed fragmented response. Fragmentation or scattering of tumour cells also causes a clear discrepancy between macroscopy and microscopy [71].…”
Section: Patterns Of Tumour Response: Fragmentation Versus Shrinkagementioning
confidence: 95%
See 3 more Smart Citations